REUSE OF WASTEWATER FROM POLYESTER FIBRES DYEING PROCESS BY THERMAL FIXATION WITH DYE ACID BASE: CASE STUDY IN A BRAZILIAN AUTO PARTS FACILITY - Lamas, W. Q.; Fujisawa, R. S. (Revista de Engenharia Térmica, 2009)
This work aims to test biodegradable chemicals into treatment of textile waste water from an auto parts facility with goal of reuse of water treated in dyeing process of lace used in safety belts. It presents a method that suits the treatment of waste water with local environmental regulations and allows the reuse of water through the adoption of actions that replace the conventional physical-chemical treatment by biodegradable products, which naturally extend the possibility of reuse beyond the process and increase the quality of water for reuse in that one, allowing satisfy the requirements of product quality demanded by the market. This work proposes substitution of some chemicals by biodegradable products and comparison to previous results obtained with current treatment for the same conditions preestablished. Also the ultra-filtration method had evaluated and its results were compared to traditional process and to new proposal. According to results obtained, replacement of traditional chemicals by biodegradable products is technical and economical viable and attends to the waste water reuse policy proposed.